PENDEKATAN PERMAINAN TRADISIONAL MUTEL UNTUK MENINGKATKAN HASIL BELAJAR TENTANG LINGKARAN - Ajawaila, Syami; Mataheru, Wilmintjie; Ngilawajan, Darma Andreas (Jurnal Pendidikan Matematika (JUPITEK), 2019)
This study aims to improve student learning outcomes about circles topics in mathematics through the traditional game namely marbles. The research has been conducted using experiments method with Posttest Only Control Group Design. Students of grade eight in SMP Negeri 2 Nusalaut, Central Maluku Regency were subject, where students in class VIII1 as an experiment class and using marbles while students at class VIII2 as a conventional class. Data were collected from the essay test and it was analyzed by descriptive statistics and inferential statistics. The results showed that the average of students learning outcomes in the class experiment is 74.43 and the average of learning outcomes of class control is 64.50. It means that the learning outcomes of students who taught by using approach the traditional game marbles increase compared with the learning outcomes of students taught by conventional approaches